ENVIRONMENTAL MANAGEMENT OF THE USE OF NATURAL RESOURCES IN THE SUSTAINABLE DEVELOPMENT OF THE NATIONAL ECONOMY OF UZBEKISTAN - Ilkhom, Nosirov; Ermatov, Ilmidin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
One of the most important tasks facing the general principles of environmental management, and one of the most important tasks facing our country, is to ensure its socio-economic efficiency. Therefore, the widespread development of the environmental management system is becoming important in the socio-economic development of our country in the coming years. The aim of this study is also to create ecological mills for management, as well as environmental management, which will be used to achieve economic stability.